2008
DOI: 10.1242/jcs.028654
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed cyclophilin B suppresses apoptosis associated with ROS and Ca2+ homeostasis after ER stress

Abstract: Prolonged accumulation of misfolded proteins in the endoplasmic reticulum (ER) results in ER stress-mediated apoptosis. Cyclophilins are protein chaperones that accelerate the rate of protein folding through their peptidyl-prolyl cis-trans isomerase (PPIase) activity. In this study, we demonstrated that ER stress activates the expression of the ER-localized cyclophilin B (CypB) gene through a novel ER stress response element. Overexpression of wild-type CypB attenuated ER stress-induced cell death, whereas ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 48 publications
3
94
0
Order By: Relevance
“…In addition, the observed reduction of cyclophilin B, which facilitates protein folding via its peptidyl-prolyl isomerase activity, further contributes to the failure of the ER adaptive response in this model. 29 In an earlier study, we found marked reduction of nuclear translocation of Nrf2 and downregulation of the antioxidant and cytoprotective byproducts of its target genes in the kidneys of Imai rats. 22 In confirmation of the latter study, we found marked reduction of nuclear Nrf2 content in the untreated Imai rat kidneys.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the observed reduction of cyclophilin B, which facilitates protein folding via its peptidyl-prolyl isomerase activity, further contributes to the failure of the ER adaptive response in this model. 29 In an earlier study, we found marked reduction of nuclear translocation of Nrf2 and downregulation of the antioxidant and cytoprotective byproducts of its target genes in the kidneys of Imai rats. 22 In confirmation of the latter study, we found marked reduction of nuclear Nrf2 content in the untreated Imai rat kidneys.…”
Section: Discussionmentioning
confidence: 76%
“…GST-CypB and CypB series region reporter plasmids have been described previously. 10 The active-ATF6 expression vector was kindly provided by Dr. Kyung Ho Lee (Konkuk University, Seoul, Korea). The human CHOP promoter reporter constructs were kindly provided by Dr. P Fafournoux (Unité Nutrition Humaine, INRA de Theix, Champanelle, France).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that Cyclophilin B (CypB) blocks Ca 2 þ leakage from the ER to cytosol against the ER stress-inducing drug, thapsigargin (Ca 2 þ ATPase (SERCA) blocker), and ultimately prevents cell death in response to ER stress. 10 However, the exact molecular mechanism by which CypB protects against ER stress is still elusive.…”
mentioning
confidence: 99%
“…Conventional ChIP was conducted as described previously [46], except that cross-linked H9c2 chromatin was subjected to immunoprecipitation with an antibody against the p65 subunit of NF-κB. The MnSOD promoter containing a binding site of NF-κB was amplified using the following primers: forward, 5′-CCCTCCTGGTAACAGTGTTAG-3′ and reverse, 5′-GCCTACTAAGGATGACTGGG-3′.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%